The global burden of antimicrobial resistance: urinary tract infections - Vietinghoff, Sibylle von; Shevchuk, Olga; Dobrindt, Ulrich; Engel, Daniel Robert; Jorch, Selina K.; Kurts, Christian; Miethke, Thomas; Wagenlehner, Florian (Nephrology, dialysis, transplantation, 2024)
Antimicrobial resistance (AMR) has emerged as a significant global healthcare problem. Antibiotic use has accelerated the physiologic process of AMR, particularly in Gram-negative pathogens. Urinary tract infections (UTIs) are predominantly of a Gram-negative nature. Uropathogens are evolutionarily highly adapted and selected strains with specific virulence factors, suggesting common mechanisms in how bacterial cells acquire virulence and AMR factors. The simultaneous increase in resistance and virulence is a complex and context-dependent phenomenon. Among known AMR mechanisms, the plenitude of different β-lactamases is especially prominent. The risk for AMR in UTIs varies in different patient populations. A history of antibiotic consumption and the physiology of urinary flow are major factors that shape AMR prevalence. The urinary tract is in close crosstalk with the microbiome of other compartments, including the gut and genital tracts. In addition, pharmacokinetic properties and the physiochemical composition of urinary compartments can contribute to the emergence of AMR. Alternatives to antibiotic treatment and a broader approach to address bacterial infections are needed. Among the various alternatives studied, antimicrobial peptides and bacteriophage treatment appear to be highly promising approaches. We herein summarize the present knowledge of clinical and microbiological AMR in UTIs and discuss innovative approaches, namely new risk prediction tools and the use of non-antibiotic approaches to defend against uropathogenic microbes.
Online verfügbar: 27 October 2023
Gesehen am 29.07.2024